Asimilasi Atraksi Budaya Dan Edukasi Dalam Museum Tokoh Surabaya - M. Bima Rizqi; Aldi Saputra; Rizky Putra E; Mohammad Insan Romadhan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Museum do not merely function as space for preserving historical atifacts, but also serve as educational arenas capable of conveying cultural and national values. This article examines the assimilation of cultural attractions and educational functions in three character-based museums in Surabaya: the HOS Tjokroaminoto Museum, the dr. Soetomo Museum, and the Surabaya Education Museums. This study emplyos a qualitative method with a descriptive approach, using content analysis to observe atifact, visual media, and historical narrative presanted in each museum. The findings hightlight that the assimilation of cultural attractions and educational elements within museums can serve as a strategic model for developing cultural policies that are more participatory, relevant, and contextual. This, museums are not only place to commemorate the past but also act as platform for shaping character and historical awereness among younger generations.